Réponses

Meilleure réponse !
2013-12-07T09:46:27+01:00
Bonjour,

Exercice 4

A=\dfrac{11}{4}x(8x-10)\\\\A=\dfrac{11}{4}x\times8x-\dfrac{11}{4}x\times10\\\\A=22x^2-\dfrac{55}{2}x

B = (x + 9)(3 - 2x) = 3x - 2x² + 27 - 18x
   = -2x² - 15x + 27

C = (3y + 5)(10 + y)
   = 30y + 3y² + 50 + 5y
   = 3y² + 35y + 50

D = (z - 2)(3 - z)
   = 3z - z² - 6 + 2z
   = -z² + 5z - 6

E = 5(3g + 1)(g - 2)
   = 5(3g² - 6g + g - 2)
   = 5(3g² - 5g - 2)
   = 15g² - 25g - 10

F = (2x - 1)(x² + 3)
   = 2x^3 + 6x - x² - 3
   = 2x^3 - x² + 6x - 3

Exercice 5 

A=\dfrac{7}{3}(6x+3) + \dfrac{5}{2}(4 - 2x)\\\\A = 14x+7+10-5x\\\\A=9x+17

B = 4(1 - 7y) + (4y - 5)(y - 1)
   = (4 - 28y) + (4y² - 4y - 5y + 5)
   = 4 - 28y + 4y² - 4y - 5y + 5
   = 4y² - 37y + 9

C = 3t(t + 1) + (5 + t)(t - 2)
    = (3t² + 3t) + (5t - 10 + t² - 2t)
    = 3t² + 3t + 5t - 10 + t² - 2t
    = 4t² + 6t - 10

D = (4k - 1)(9 + k) - 9k(10 - 3k)
    = 36k + 4k² - 9 - k - 90k + 27k²
    = 31k² -55k - 9

E = (m + 2)(8 + 3m) - 2(1 - m)(m - 7)
   = (8m + 3m² + 16 + 6m) - 2(m - 7 - m² + 7m)
   = 8m + 3m² + 16 + 6m - 2m + 14 + 2m² - 14m
   = 5m² -2m + 30